Al Mawsu'at al Jughrafiyyah li al 'alam al Islamiy = The Geographical Encyclopedia of the Muslim World - Al Mawsu'at... (Al Mamlakat al 'Arabiyyah al su'udiyyah Wazirat al ta'lim al 'Aliy, 1999)
ws17/ws.jl.1,4-13,15,c.1, jl.2,3,14 [bg.1-2]c.1